Accomplishing adaptability in simulation frameworks: the bubble approach - Díaz Pace, J. Andrés (2000)
Enforcing framework adaptability is one of the key points in the process of building an object-oriented application framework. When it comes to simulation, some adaptation mechanisms to configure components on-the-fly are usually required in order to produce good software artifacts and alleviate development effort. The paper reports an experience using a simulation multi-agent framework, initially conceived to be used in fluid flow problems. The framework architecture demonstrated during its evolution a great potential regarding to flexibility and modularity, tackling a wide range of other problems ranging from a network protocol simulation to a soccer simulation